2011
DOI: 10.4028/www.scientific.net/kem.460-461.106
|View full text |Cite
|
Sign up to set email alerts
|

A GA Based Measurement Method for Discontinuous Curve Fitting

Abstract: Discontinuous curve fitting is the task of finding a suitable function which is best fitting to a given set of data points. Once the expression forms of function and of error are determined, curve fitting is regarded as an optimization problem. In this paper, a measurement method is proposed to optimize curve fitting problem. The proposed method is based on genetic algorithm, namely GAOCF (GA based Optimizer for Curve Fitting). The main advantage is that the proposed GA based method can skip the local optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…They are presented in Table I, along with related information and references to methods with full automation potential. 39,118…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…They are presented in Table I, along with related information and references to methods with full automation potential. 39,118…”
Section: Theorymentioning
confidence: 99%
“…95,126,129 However, peak parameter estimation requires initial estimates of the very same parameters; these can be difficult to gauge, 94 and unless guesses are very good, variations in initial parameters can lead to widely varying results. 93,130 The requisite initial estimates can be based on derivatives, 94 principal component analysis, 99 two-dimensional peak finding, 93 biologically inspired procedures, 92,100 monitoring changes in fitting errors as a function of minimum separable peak-peak distances, 95 and wavelet transforms, 97 among others. Both Lorentzian distributions (also known as Student's t-distributions with one degree of freedom or Cauchy distributions or Breit-Wigner distributions) and Gaussian distributions have been used for vibrational band curve fitting.…”
mentioning
confidence: 99%
“…Methods used to estimate the number of bands include derivative approaches 20 and principal component analysis. 22 Methods used to estimate initial band parameters include two-dimensional peak finding, 15 biologically inspired parameter-finding procedures, 23,24 monitoring changes in fitting errors as a function of minimum separable peak–peak distances, 19 Fourier self-deconvolution and maximum-likelihood restoration prior to curve fitting, 25 simultaneous deconvolution and curve-parameter extraction with adaptive Tikhonov regularizaron, 26 and wavelet transforms. 27 Regarding band shapes, both Lorentzian distributions (also known as Student's t -distributions with one degree of freedom, or Cauchy or Breit–Wigner distributions) and Gaussian distributions have been used for curve fitting.…”
Section: Introductionmentioning
confidence: 99%
“…Least squares method (LSM) is a common method used to deal with optimization problems, but the obtained solutions are sometime local optimum solutions [2,9,13,14,15,18]. Previous researcher has demonstrated that genetic algorithm (GA) can effectively solve c optimization problems [3], but the coding method itself has an influence on the final results. In addition, the difficulty of parameter coding is also widely encountered in computational processes.…”
Section: Introductionmentioning
confidence: 99%